Power Characteristics of Selective Buried Oxide MOSFET - Younis, Dana Tariq (2016)
A Master of Science thesis in Electrical Engineering by Dana Tariq Younis entitled, "Power Characteristics of Selective Buried Oxide MOSFET," submitted in January 2016. Thesis advisor is Dr. Hasan Al-Nashash. Soft and hard copy available.